Peran Kepemimpinan dalam Manajemen Perbaikan Status Gizi: Tinjauan Pustaka - Agustiawan, Agustiawan (Yayasan Literasi Sains Indonesia, 2025)
Nutrition Leadership and Nutrition Program Management is a leadership and network-based program that focuses on enhancing the capacity of individuals to become skilled professionals and leaders in the field of human nutrition. Leadership in nutrition is an emerging state and country-level data are lacking. Broader reviews looking beyond the discipline have emphasized the need for a contextual understanding of how leaders operate, without losing sight of the individual skills needed to negotiate complex issues and equally complex policy environments. The two FAO recommended actions that are least implemented at the country level are nutrition situation analysis and nutrition promotion. These two actions are also least frequently included in documents developed by subregional institutions. This is not surprising as technical competence for these actions is often lacking in the agricultural sector. Cross-sectoral collaboration and value-added are two other recommendations that are rarely included in regional/institutional documents. Given the difficulties faced in vertical and horizontal coordination not only by country but also at the regional level, this is also a significant barrier to creating synergies that can foster better linkages between agriculture and nutrition.